High thermal conductivity hot work tool steel powder for additive manufacturing with excellent hardenability and mold cracking resistance and lamination molded body therewith
The optimized hot tool steel powder composition addresses cracking and thermal conductivity limitations in additive manufacturing, enabling large-scale production with uniform hardness and improved quenchability for larger models.
Patent Information
- Application Number
- JP2023121766
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2043-07-26
AI Technical Summary
Conventional additive manufacturing methods for hot tool steel tools are limited to small sizes due to cracking issues caused by thermal stresses, low hardenability, and insufficient thermal conductivity, which restrict their application to larger models.
A hot tool steel powder composition with controlled amounts of C, Ni, Si, Mn, Cr, Mo, W, V, and Al, optimized to balance high thermal conductivity and hardenability, minimizing cracking resistance and hardness variations across the tool's depth.
The solution enables large-scale additive manufacturing with reduced cracking and enhanced thermal conductivity, allowing for uniform hardness distribution and improved quenchability, suitable for larger models without cracking.
Smart Images

Figure 2025018233000001 
Figure 2025018233000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot work tool steel powder with high thermal conductivity for additive manufacturing and an additive manufactured body using the same. That is, the present invention relates to a molded body and raw material powder that become various tools such as dies by additive manufacturing (also called 3D printer, three-dimensional modeling method, additive manufacturing, etc.), and in particular to a hot work tool steel that exhibits sufficient hardenability, high resistance to molding cracking, high thermal conductivity, and also has high mechanical properties, even for large molded bodies.
[0002] Here, high resistance to molding cracking refers to the fact that cracks are less likely to occur in the molded body itself (especially in areas that become notched) or at the interface between the molded body and the base material due to thermal stress associated with rapid melting and solidification during additive manufacturing. [Background technology]
[0003] Unlike conventional manufacturing methods, additive manufacturing is capable of manufacturing components with complex shapes and three-dimensional structures, and in recent years has seen remarkable technological development and an expansion in the range of applications. Attempts are being made to apply additive manufacturing to various tools, and in particular, efforts are being made to put it to practical use in die-casting molds that have complex cooling water pipes with three-dimensional structures inside.
[0004] Now, tools using hot work tool steel are used to process various parts, and their shapes and sizes vary depending on the processing method and part shape. However, the application of additive manufacturing to tools has had to be limited to relatively small ones due to the following molding cracks.
[0005] In general, additive manufacturing involves heating the raw material powder or wire with a narrowly focused heat source such as a laser or electron beam for a short period of time, causing it to melt and solidify rapidly, and then repeating this process to build up solidified layers, making it possible to manufacture parts with complex three-dimensional shapes. In this process, only a portion of the part is heated, melted, and solidified, which generates thermal stress due to localized solidification and shrinkage and thermal expansion and contraction. If the material being modeled or the base material is hard and brittle, it will not be able to withstand the thermal stress that is generated, and model cracks will occur in the model itself or at the interface with the base material.
[0006] This type of thermal stress becomes even greater when a large object is additively manufactured, resulting in more likely cracks during manufacturing. Generally, tools are made of high-hardness alloys such as JIS standard SKD61, which are prone to cracks during manufacturing. For these reasons, the application of additive manufacturing to tools has traditionally been limited to small tools that experience relatively little thermal stress.
[0007] The surfaces of hot tools, including die-casting dies, are susceptible to heat checking and other damage due to the temperature rise caused by contact with the hot parts (workpieces) being processed. Furthermore, areas where the temperature rise is particularly rapid are prone to seizure.
[0008] In order to avoid these problems, it is important to efficiently cool the surface of the hot work tool. By using an alloy with high thermal conductivity as the material for the hot work tool, the cooling effect of water-cooled pipes placed inside the tool can be maximized all the way to the hot work tool surface.
[0009] Furthermore, when machining parts using hot tools, the tools need to cool after machining one part and before machining the next part. Therefore, being able to efficiently (in a short time) cool the tools to a specified temperature has the benefit of shortening the part machining cycle and improving part production efficiency.
[0010] As a laminated structure made of hot work tool steel with such high thermal conductivity, the applicant has proposed, for example, a structure made of an Fe-based alloy powder containing, by mass%, 0.20 < C < 0.60, Si < 0.60, Mn < 0.90, Cr < 4.00, Ni < 2.00, Mo < 1.20, W < 2.00, V < 0.60, Al < 0.10, with the balance being Fe and inevitable impurities, which satisfies the following formulas (1) to (3) (see Patent Document 1). T1 = 71.7 - 5.9Mn - 6.3Cr - 2.8V - 5.7Mo - 1.1W - 23.1C - 5.8Ni - 1.9Si - 0.5Al - 0.6P > 32.0 ··· Formula (1) T2 = 80.1 + 2.4Mn + 1.6Si + 7.1Cr - 12.0P > 50.0 ··· Formula (2) Average size (μm) of carbides contained in the structure: P < 3.0 ··· Formula (3)
Prior Art Documents
Patent Documents
[0011]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0012] In the above-mentioned Patent Document 1, since the thermal conductivity decreases with an increase in the addition amounts of various elements, it attempts to achieve high thermal conductivity by defining the addition amounts of these elements and the upper limits of the T1 parameter. That is, compared with SKD61, which is a general-purpose steel widely used as a hot work tool, it attempts to obtain high thermal conductivity by reducing the amounts of each added element.
[0013] However, since various added elements also contribute to improving hardenability, a decrease in the addition amounts of these elements simultaneously leads to a decrease in hardenability.
[0014] In the past, from the viewpoint of the occurrence of molding cracks due to thermal stress, additive manufacturing had to be limited to relatively small hot tools in practical applications. Therefore, in the deep parts of large tools, the cooling speed during quenching is not sufficient (sufficient quenching and tempering hardness is not obtained). Even if an alloy with relatively low hardenability is used, it can be applied without problems arising because the molded body is relatively small.
[0015] However, in order to meet the recent trend of expanding the range of applications for tools made by additive manufacturing and the demand for using additively manufactured bodies for larger hot working tools, it is necessary to achieve a high level of both hardenability and high thermal conductivity, which are in a trade-off relationship depending on the amount of various added elements. Conventional alloys were not able to maintain both properties at a high level.
[0016] In addition, because additive manufacturing is a rapid cooling method, the molded product may be in a pseudo-hardened state, and may be used after only tempering or distortion relief heat treatment without further hardening after molding. However, heat accumulates in the center of the large molded product from the heat source of the molding, causing the temperature to rise, making it difficult to achieve the rapid cooling effect despite the rapid cooling method, and alloys with low hardenability tend to have low hardness in the deep parts of the molded product, which hinders the size of the product.
[0017] Furthermore, it is known that preheating the base material during printing can reduce cracks, but due to the design of the printing equipment, a preheating temperature of around 80 to 300°C is often used. In this case, the effect of rapid cooling during printing is less pronounced not only for large but also for small objects, and with alloys with low hardenability, the hardness of the deep parts of the objects tends to be low, which is a problem.
[0018] In addition, the optimal hardness of each tool varies depending on the application, with some applications requiring around 40HRC and others requiring around 50HRC, but if the hardness differs between the surface and the deeper layers due to poor hardenability, it becomes difficult to adjust the entire tool to the optimal hardness, resulting in defects. Therefore, in addition to the absolute hardness value, it is also important to reduce the variation in hardness depending on the part.
[0019] In view of the above, the present invention aims to provide a hot working tool steel powder for additive manufacturing, which is easy to harden deep into even in large-scale additive manufacturing, is less likely to cause cracks at the molded body and the interface between the molded body and the additive base material, and has high thermal conductivity, and an additive manufacturing body made using the same. [Means for solving the problem]
[0020] In light of the above background, the inventors have intensively developed the components of a hot work tool steel for additive manufacturing that has sufficient hardenability and high thermal conductivity to provide sufficient hardenable hardness even for large objects, and have focused on Ni as an element that can achieve high hardenability while minimizing the decrease in thermal conductivity.As a result of their investigations, they have found that by strictly specifying the amounts of Ni and Cr added, it is possible to achieve a high level of compatibility between these two properties, thereby arriving at the present invention.
[0021] Furthermore, as described above, in large-scale additive manufacturing, the thermal stress generated increases and molding cracks become more likely to occur, but it was discovered that by specifying the amount of Ni, Cr, and C added, the hardness of the molded object can be reduced and the resistance to molding cracks is also excellent. In other words, the present invention is practically applicable to larger molded objects compared to the conventional method, which has been mainly applied to small molded objects, and the present invention has been improved to an alloy that improves hardenability by optimizing the range of the amounts of Ni, Cr, and C added, minimizes the decrease in thermal conductivity, and is not prone to molding cracks even in large-scale molding.
[0022] Therefore, the first means for solving the problems of the present invention is a hot work tool steel powder for additive manufacturing having, in mass%, as essential added components: C: more than 0.10% and less than 0.45%, Ni: more than 2.00% and less than 8.00%, and as optional added components: Si: less than 0.60%, Mn: less than 5.00%, Cr: less than 2.00%, Mo: less than 1.20%, W: less than 2.00%, V: less than 0.60%, Al: less than 0.10%, with the balance being Fe and unavoidable impurities, and Ni+Mn: less than 8.50%.
[0023] The second aspect of the present invention is a shaped body produced by additive manufacturing using the hot working tool steel powder for additive manufacturing described in the first aspect. Effect of the Invention
[0024] According to the means of the present invention, it is possible to provide a hot work tool steel powder for additive manufacturing, which is easy to harden deep even in large-scale additive manufacturing, is less likely to cause cracks at the interface between the molded body and the additive base material, and has high thermal conductivity, and an additive manufacturing body using the same.
[0025] Furthermore, the means of the present invention can exert excellent effects, such as being able to achieve both high hardenability and high thermal conductivity, even when applied to processes in which hardening is omitted, small-scale molding, or cases in which a molded body is obtained in a preheated molding process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Before describing the embodiments of the present invention, the reasons for specifying the components of the hot work tool steel powder for additive manufacturing used in the shaped body of the present invention will be described. Note that % for each component is mass %. The remainder of the components is Fe and unavoidable impurities.
[0027] C: More than 0.10% to less than 0.45% C is an essential component for obtaining high quenching and tempering hardness by dissolving in the martensite phase, which is the matrix, and precipitating fine carbides. However, if C is 0.10% or less, high quenching and tempering hardness cannot be obtained. From this viewpoint, C is made to exceed 0.10%. Preferably, C is made to exceed 0.20%, and more preferably, C is made to exceed 0.30%. On the other hand, if C is 0.45% or more, the hardness as molded becomes excessively high, and the effect of deteriorating mold cracking resistance is relatively large compared to other components, and the amount of solid solution C increases and the thermal conductivity decreases. Therefore, C is made to be less than 0.45%. Preferably, C is less than 0.42%, and more preferably, C is less than 0.40%.
[0028] Ni: Over 2.00% to less than 8.00% Ni is an essential component for improving hardenability and improving the quenching and tempering hardness even in the deep part of a large shaped body, and is the most important component in the present invention because it has a relatively small effect on reducing thermal conductivity compared to other components. Ni also has the effect of delaying martensite transformation during cooling during shaping, and has the effect of improving resistance to shaping cracking by maintaining austenite, which is soft and resistant to shaping cracking, at a relatively low temperature. However, if Ni is 2.00% or less, the effect is insufficient, so Ni is made to be more than 2.00%. From this viewpoint, Ni is preferably more than 2.30%, and more preferably Ni is more than 3.00%. On the other hand, if Ni is 8.00% or more, the amount of solid solution in the matrix increases, greatly reducing the thermal conductivity. Therefore, Ni is made to be less than 8.00%. Ni is preferably less than 6.50%, and more preferably Ni is less than 5.00%.
[0029] Si: Less than 0.60% Si is a component that improves hardness by dissolving in the matrix. It also has the effect of improving softening resistance. Therefore, the Si content is set to 0 to less than 0.60%. However, when the Si content is 0.60% or more, the amount of dissolved Si increases and the thermal conductivity is significantly reduced. Therefore, the upper limit of Si is set to less than 0.60%. Preferably, Si is less than 0.40%, and more preferably, Si is less than 0.24%. On the other hand, although Si may be 0%, since Si is a component that improves hardness and softening resistance, when Si is added, it is preferably more than 0.04%, and more preferably more than 0.10%.
[0030] Mn: Less than 5.00% Mn is a component that improves hardenability and improves the quenching and tempering hardness even in the deep part of a large shaped body. It also has the effect of improving softening resistance. Therefore, Mn is set to 0 to less than 5.00%. However, if Mn is 5.00% or more, the amount of solid-solubilized Mn increases and the thermal conductivity decreases. Therefore, Mn is set to less than 5.00%. Preferably, Mn is less than 1.00%, and more preferably, Mn is less than 0.41%. On the other hand, Mn may be 0%, but when Mn is added, from the viewpoint of improving the deep quenching and tempering hardness and improving the softening resistance, Mn is preferably more than 0.05%, and more preferably, Mn is more than 0.11%.
[0031] Ni+Mn: Less than 8.50% Mn is also a component that has an effect similar to that of Ni. Therefore, if the total amount of Mn and Ni is 8.50% or more, the amount of solid solution in the matrix increases, significantly decreasing the thermal conductivity. Therefore, Ni+Mn is set to less than 8.50%. Preferably, Ni+Mn is less than 7.00%, and more preferably less than 5.00%.
[0032] Cr: Less than 2.00% Cr is a component that improves hardenability and improves the quenching and tempering hardness even in the deep part of a large shaped body. It also has the effect of improving softening resistance. However, when Cr is 2.00% or more, the amount of dissolved Cr increases and the thermal conductivity decreases, and the effect of the decrease is relatively large compared to other components. Therefore, Cr is set to 0 to less than 2.00%. Preferably, Cr is less than 1.50%, and more preferably, Cr is less than 1.15%. Cr may be 0%, but since Cr is a component that improves hardenability and improves the quenching and tempering hardness even in the deep part of a large shaped body, and also has the effect of improving softening resistance, when Cr is added, it is preferably more than 0.50%, and more preferably more than 0.85%.
[0033] Mo: Less than 1.20% Mo is a component that promotes secondary hardening during tempering and increases the hardness after quenching and tempering. Although Mo reduces thermal conductivity by addition, its contribution is small, and its effect of improving hardness is large. Therefore, Mo is set to 0 to less than 1.20%. Mo is preferably less than 1.05%, and more preferably less than 0.95%. Mo may be 0%, but when Mo is added, it promotes secondary hardening during tempering and increases the hardness after quenching and tempering, while reducing thermal conductivity by addition, its contribution is small, and its effect of improving hardness is large, so Mo is preferably set to more than 0.60%, and more preferably set to more than 0.75%.
[0034] W: Less than 2.00% W is a component that promotes secondary hardening during tempering and increases the hardness after quenching and tempering. Although W reduces thermal conductivity by its addition, its contribution is small, and its effect of improving hardness is large. Therefore, W is set to 0 to less than 2.00%. W is preferably less than 1.00%, and more preferably less than 0.50%. W may be 0%, but since W is a component that promotes secondary hardening during tempering and increases the hardness after quenching and tempering, and although its addition reduces thermal conductivity by its addition, its contribution is small, and its effect of improving hardness is large, when W is added, W is preferably more than 0.05%, and more preferably more than 0.10%.
[0035] V: Less than 0.60% V is a component that promotes secondary hardening during tempering and increases quenching and tempering hardness, but excessive addition reduces thermal conductivity. Therefore, V is set to 0 to less than 0.60%. V is preferably less than 0.55%, and more preferably less than 0.50%. V may be 0%, but since V is a component that promotes secondary hardening during tempering and increases quenching and tempering hardness, when V is added, V is preferably more than 0.20%, and more preferably more than 0.30%.
[0036] Al: Less than 0.10% Al is a component that forms nitrides and suppresses the coarsening of crystal grains during quenching. However, when Al is added at 0.10% or more, the toughness decreases due to the formation of excess Al nitrides. It also reduces thermal conductivity. Therefore, Al is set to 0 to less than 0.10%. Preferably, Al is less than 0.07%, more preferably less than 0.04%. Although Al may be 0%, Al is a component that forms nitrides and suppresses the coarsening of crystal grains during quenching, so when Al is added, Al is preferably more than 0.001%, more preferably more than 0.002%. Note that Al may not be intentionally added, but may be mixed in from refractories used for melting gas atomization, and the effect of containing Al is the same in either case.
[0037] (Example) Table 1 shows the composition of the steel powders of Examples No. 1 to 19 of the present invention and Comparative Examples No. 1 to 6 (the values are in mass%). The balance is Fe and unavoidable impurities. Furthermore, these Examples are merely examples of the embodiments of the present invention, and the scope of the claims is not limited to these.
[0038] [Table 1]
[0039] [Production of raw powder] As the hot work tool steel powder for additive manufacturing of the present invention, powders having the composition shown in Table 1 were obtained by gas atomization. The composition of the molded body after additive manufacturing using these powders is also the same as the composition of these powders. The specific manufacturing procedure of the powder is as follows. First, the molten raw material charged in an alumina crucible was melted by high-frequency heating in a vacuum and argon atmosphere. This molten alloy was poured from a nozzle with a diameter of 5 mm at the bottom of the crucible and immediately sprayed with high-pressure argon gas. The molten alloy was divided into fine droplets by this spraying, and cooled and solidified while falling inside the tower of the atomization device, becoming alloy powder. This alloy powder was sieved through a net with an opening of 63 μm, and the powder on the lower side that passed through the sieve was used as the raw material powder in the subsequent additive manufacturing.
[0040] [Additive Manufacturing] The additive manufacturing was carried out using a laser-heated powder bed type device (product name: EOS-M290) with a preheating temperature of 180°C, which is equivalent to the standard manufacturing conditions for maraging steel (MS1 conditions) specified for the device.
[0041] The base material for the molding was an annealed S45C plate, on which a cylinder with a diameter of 180 mm and a height of 120 mm (with a curvature of R10 on the outer periphery of the joint interface between the plate and the molding and on the outer periphery of the top surface of the cylinder) and a square pillar with a width of 15 mm, length of 150 mm, and height of 17 mm were molded.
[0042] [evaluation] Table 2 shows the hardness of the surface layer and the center of the molded bodies of each of the examples and comparative examples, the difference between these hardnesses, the thermal conductivity, and the presence or absence of cracks during molding.
[0043] [Table 2]
[0044] To evaluate the hardness of the surface and deep parts of the large-sized objects after quenching and tempering, a large cylinder with a diameter of 180 mm and a height of 120 mm was cut from a plate by wire cutting, quenched and tempered in an atmospheric furnace, and the Rockwell hardness of the test pieces cut out from the surface and deep parts was evaluated. For quenching, the cylinder was held at 1030°C for 1 hour and oil-cooled. Then, for tempering, the cylinder was held at 600°C for 4 hours and air-cooled. The same tempering process was carried out twice. (In Examples 18 and 19, quenching was not carried out, and only tempering was carried out.) From the outermost periphery and center of the large cylinders after quenching and tempering, 10 mm square blocks were cut out, and the Rockwell hardness was measured.
[0045] In addition, the optimum hardness for use of various tools varies depending on the application; there are applications where around 40HRC is preferable, and applications where around 50HRC is preferable; however, if the hardness differs between the surface and deeper parts due to poor hardenability, it becomes difficult to adjust the entire tool to the optimum hardness for use, which can lead to malfunctions. Therefore, in addition to the absolute hardness value, the variation in hardness depending on the part was evaluated as the difference in hardness between the surface and center.
[0046] Similarly, the thermal conductivity was measured using a test piece cut from the outermost part at the center of the height of a large cylinder after quenching and tempering.The thermal conductivity at room temperature was measured using the laser flash method using a test piece finished into a disk shape with a diameter of 5 mm and a thickness of 1 mm.
[0047] In addition, since the alloys were rapidly cooled and solidified, in some of the examples (Nos. 18 and 19), the hardening and thermal conductivity were not performed, and only tempering was performed.
[0048] To evaluate the resistance to molding cracking, a square pillar measuring 15 mm wide, 150 mm long, and 17 mm high was used. This square pillar does not have a curvature at the interface with the plate like a large cylinder, so the interface is at a right angle and thermal stress is concentrated at this location. Thermal stress also increases in the longitudinal direction where the amount of thermal deformation is large. As a result, in the case of a molded object with low resistance to molding cracking, molding cracks occur at the interface between the plate and the molded object at the end of the 150 mm length. Therefore, this area was visually inspected with a magnifying glass to evaluate the resistance to molding cracking based on the presence or absence of cracks and their length.
[0049] The molded bodies of Examples 1 to 19 of the present invention all have excellent surface and center hardness of 40HRC or more, the difference between the surface and center hardness is within 1.5HRC, suppressing the hardness variation, and the thermal conductivity is 25W / m / K or more (most of them are 30W / m / K or more), so they are excellent in both hardness and thermal conductivity. In addition, no molding cracks were observed in most cases, and even if a molding crack was observed, the length of the crack was only 0.5mm, showing excellent resistance to molding cracks.
[0050] Comparative Examples Nos. 1 and 2 contained insufficient Ni, and the hardness of the center and surface of the molded body varied, resulting in large molding cracks. Comparative Example No. 3 contained an excessive amount of Ni, and had a low thermal conductivity. Comparative Example No. 4 contained an excessive amount of Cr, resulting in low thermal conductivity. Comparative Example No. 5 had an insufficient amount of C, and the shaped body had low hardness. Comparative Example No. 6 had an excessive amount of C, and large molding cracks were observed.
Claims
1. In mass percent, As an essential ingredient, C: more than 0.10% to less than 0.45%; Ni: more than 2.00% to less than 8.00%; Optionally, Si: less than 0.60%; Mn: less than 5.00%; Cr: less than 2.00%; Mo: less than 1.20% W: less than 2.00% V: less than 0.60% Al: less than 0.10%; The balance consists of Fe and unavoidable impurities, and Ni+Mn: less than 8.50% Hot work tool steel powder for additive manufacturing.
2. A shaped body produced by additive manufacturing using the hot working tool steel powder for additive manufacturing according to claim 1.
Citation Information
Patent Citations
High-strength and high-toughness cr alloy steel powder sintered compact and its production
JP1994306403A
Iron-based powdery mixture for powder metallurgy and production method therefor, and sintered compact excellent in tensile strength and shock resistance
JP2018123428A
High-strength and high-toughness iron-based alloy, and method for manufacturing the same
JP2022035110A
Cost-effective method for obtaining complex shaped parts.
JP2023520297A
Shaped body formed from powder
JP2022092524A